Collaborative Governance in Supervising Foreign Nationals: A Case Study of the Class I Immigration Office with Immigration Checkpoint (TPI) Tanjungpinang - Lia Andini; Kusmartono Wibowo (Journal Governance Bureaucratic Review, 2026)
This article examines collaborative governance in the supervision of foreign nationals through a qualitative case study of the Class I Immigration Office with Immigration Checkpoint (TPI) Tanjungpinang, Indonesia. Located in the Riau Islands, Tanjungpinang occupies a strategic border-island position marked by maritime mobility, port-based circulation, tourism, investment flows, education mobility, and cross-border social relations. These conditions make immigration supervision a multidimensional public task that cannot be performed effectively by immigration officials alone. The study analyses how institutional actors, local government units, law-enforcement agencies, accommodation providers, community informants, port operators, and knowledge institutions interact in identifying, preventing, and responding to immigration violations. Drawing on collaborative governance, public value, network governance, and adaptive digital governance literature, the article shows that effective supervision depends on four mutually reinforcing elements: role clarity, trusted information exchange, risk-based operational coordination, and continuous evaluation. The findings indicate that TIMPORA-style collaboration strengthens surveillance capacity, but its performance is constrained by unequal data quality, uneven participation by non-state actors, fragmented communication channels, and limited feedback mechanisms. The article proposes an accountable, risk-based collaborative supervision model that integrates administrative monitoring, field verification, digital reporting, and community-based early warning while maintaining proportionality and human-rights safeguards. The study contributes to collaborative governance scholarship by applying evaluation-oriented network analysis to immigration control in a maritime border context and by demonstrating that supervision of foreign nationals should be understood as a public value creation process rather than merely an enforcement function.